PENERAPAN STRATEGI CATALISTING UNTUK MENINGKATKAN KEMAMPUAN MENULIS ESAI - Setyawan Pujiono (LITERA, 2011)
This study aims to improve students’ essay writing skills at the stages of contentdevelopment, organization, and essay development using the catalisting strategy.This was an action research study involving the students of Class A of JPBSI FBSUNY enrolled in 2009 attending the Factual Writing course. The data were collected through observations, interviews, and documents. The instruments included a field note guide, an interview guide, a scoring rubric, and a questionnaire. The resultsshowed that there was an improvement of the students’ skills in developing contents, organizing problems, and developing the essay. In the problem organization, the students were capable of finding new problems and organizing them in a logicalessay outline. In the essay development, they managed to develop the essay in a logical sequence of problems and effective sentences with few errors in spelling and punctuation.